Socioeconomic Struggles and Moral Dilemmas: Impact of War in Naguib Mahfouz’s 'Midaq Alley' - Shafique, Quratul ain; Khatoon, Yasmeen; Dar, HM Usman (Pakistan Languages and Humanities Review, 2024)
War with its manifestations of horror, death and destruction has always been a recurring subject in literature. It has inspired the authors from around the world to create masterpieces depicting its aftermaths. Naguib Mahfouz’s timeless novel, ‘Midaq Alley’ relates the story of a society struggling with the vices and virtues of its people .These poor souls resist against poverty, corruption and crime against the backdrop of World War II. Although war has been depicted as a continuous phenomenon in the novel, its effects have been described implicitly by Mahfouz. This paper focuses on Naguib Mahfouz’s depiction of various characters of ‘Midaq Alley’ as they respond to an ongoing war in their country; it also aims to explore the social and economic effects of modernity as it strikes in the form of a foreign culture represented by Allied Forces. Though we do not witness any casualties as portrayed in other war novels, yet we observe an overall demise of morality, traditions and values of a nation, of which Midaq Alley is a microcosm.